2001
DOI: 10.1091/mbc.12.3.577
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Physiological Response Allows Yeast to Adapt to the Loss of the Signal Recognition Particle-dependent Protein-targeting Pathway

Abstract: Translational control has recently been recognized as an important facet of adaptive responses to various stress conditions. We describe the adaptation response of the yeast Saccharomyces cerevisiae to the loss of one of two mechanisms to target proteins to the secretory pathway. Using inducible mutants that block the signal recognition particle (SRP) pathway, we find that cells demonstrate a physiological response to the loss of the SRP pathway that includes specific changes in global gene expression. Upon in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
96
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 44 publications
4
96
0
Order By: Relevance
“…Although, these depletions are not lethal, the cells grow very slowly and exhibit 'petite' phenotype (Brown et al, 1994). Interestingly, however, the yeast SRP54-null mutant adapts to the loss of the SRP by eliciting the synthesis of chaperones and reducing the production of ribosomes (Mutka and Walter, 2001). In trypanosomes, however, silencing of each of the SRP proteins is lethal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, these depletions are not lethal, the cells grow very slowly and exhibit 'petite' phenotype (Brown et al, 1994). Interestingly, however, the yeast SRP54-null mutant adapts to the loss of the SRP by eliciting the synthesis of chaperones and reducing the production of ribosomes (Mutka and Walter, 2001). In trypanosomes, however, silencing of each of the SRP proteins is lethal.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, however, signal-peptidecontaining proteins are translocated in E. coli via the chaperone pathway (Lee and Bernstein, 2001). In yeast, the SRP pathway is essential for growth in Schizosaccharomyces pombe (Althoff et al, 1994), but not in Saccharomyces cerevisiae (Brown et al, 1994;Mutka and Walter, 2001). Nevertheless, the secretion of signal-peptide-containing proteins in both these yeast strains depends on the SRP pathway, and during its depletion these proteins are not properly translocated to the ER, suggesting that each protein has its dedicated pathway for translocation (Hann and Walter, 1991;Stirling and Hewitt, 1992;Brown et al, 1994).…”
mentioning
confidence: 99%
“…In support of this proposal, it has been demonstrated that mRNAs retain their association with the ER in the absence of ribosome engagement and thus participate in ribosome-independent interactions with components of the ER Lerner and Nicchitta 2006). The possibility that mRNAs may undergo direct targeting to the ER is also suggested by data obtained in Saccharomyces cerevisae, where genetic inactivation of the SRP pathway revealed compensatory mechanisms for continued functioning of the secretory pathway (Hann and Walter 1991;Ogg et al 1992;Mutka and Walter 2001). Relatively little is known, however, about how mRNAs encoding secretory and integral membrane proteins are localized in the intact cell and the role(s) played by the SRP pathway in directing mRNA localization to the ER.…”
Section: Introductionmentioning
confidence: 85%
“…BWY497 has a mutation in the N-terminal cytosolic domain of the Sec62, which is important for complex formation with Sec63 (16). It was reported that strains lacking functional SRP undergo physiological adaptation after 4 h of growth at nonpermissive temperature by slowing down translation (17). Hence, cells were grown overnight at low temperature (22°C) and incubated at 37°C only for 4 h followed by whole-cell lysate preparation, SDS-PAGE, and Western blotting.…”
Section: Defect In Srp Impairs Targeting Of Signal Anchor Proteins Ofmentioning
confidence: 99%